A long road to educational equity: Tracking trends through PISA 2000–2018 - Ekaterina Enchikova; Tiago Neves; Cibelle Toledo; Gil Nata (International Journal of Educational Research Open)
THE AUTHORS INFORMATION IS BLINDED: The OECD's Programme for International Student Assessment (PISA) has reported on the levels of educational equity in participating countries since its inception in 2000. However, little attention has been paid to changes in equity levels over time. This study analyses data from the 2000 to 2018 PISA rounds, offering an overview of educational socioeconomic-related equity — specifically equality of opportunity (assessed through the relationship between R-squared and ESCS) — trends across 87 countries, comprising 37 OECD members and 50 partner countries. It provides insights into the dynamics of equity levels at the country level, the stability of these trends, and the consistency of the changes. By using all available PISA waves for each participating country, calculating an average R-squared between subjects (Reading, Math and Science), and combining the “absolute” position in the equity indicator with the change over time in that same indicator, this study presents the first comprehensive picture of the evolution of equality of opportunities (assessed through the R-squared indicator) in all PISA-participating countries. Results show that, on average, PISA-participating countries have only slightly improved their equality of opportunity. Additionally, there is an absence of clear patterns regarding the relationship between equity levels and equity change, highlighting the diversity of national pathways to equity and underscoring the importance of analysing specific contexts when assessing equity. Lastly, this study also helps to identify successful country cases that have demonstrated more solid and coherent positive trends in improving educational equity over the last two decades.